Speaking anxiety among postgraduate international students in the academic context of a university in Malaysia - Taly, Bikash Chandra; Paramasivam, Shamala (Macrothink Institute, 2020)
Anxiety is common for international students when speaking in the academic context. The aim of this study is to explore the reasons that cause speaking anxiety in the academic context of a university. The study also aims to find out strategies used by students to cope with speaking anxiety. This research employs the qualitative method in the form of interview questions to investigate the issues. Fifteen international postgraduate students and two experienced university lecturers of a public university in Malaysia were interviewed through semi-structured interviews. The investigation revealed that speaking anxiety originates from students' self-related perceptions, learning challenges, differences between students' and target language cultures, poor language knowledge, and fear of being evaluated by peers and lecturers. The strategies used to cope with speaking anxiety included a variety of affective (relaxation), cognitive (positive thinking) and behavioral strategies (preparation/practice, avoidance of eye contact, providing immediate response to instructors’ questions, taking part in as many speaking activities as possible, peer seeking and physical masking behavior). From the investigation, it is found that anxiety has an influence on students’ communication when speaking in English. More emphasis should be given to anxiety reducing methods in the teaching and learning context of higher education.